Matching Unfamiliar Voices to Static and Dynamic Faces: No Evidence for a Dynamic Face Advantage in a Simultaneous Presentation Paradigm - Huestegge, Sujata M. (Frontiers in Psychology, 2019)
Previous research has demonstrated that humans are able to match unfamiliar voices to corresponding faces and vice versa. It has been suggested that this matching ability might be based on common underlying source information that has characteristic effects on both faces and voices. Some researchers have additionally assumed that dynamic facial information might be especially relevant to successfully match faces to voices. In the present study, we compared static and dynamic face-voice matching ability in a simultaneous presentation paradigm. Additionally, we implemented a procedure (matching additionally supported by incidental association learning) which allows us to reliably exclude participants that did not pay sufficient attention to the task. A comparison of performance between static and dynamic face-voice matching suggested a lack of substantial differences in matching ability for static and dynamic faces, suggesting that dynamic (as opposed to mere static) facial information does not contribute substantially to face-voice matching performance. Implications regarding the underlying mechanisms of face-voice matching are discussed.